2019
DOI: 10.1039/c9py00889f
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed anionic diblock copolymer worm gels are useful model systems for calcite occlusion studies

Abstract: Binary mixtures of RAFT macromolecular chain transfer agents are utilized to rationally design anionic diblock copolymer nanoparticles via PISA. The role of carboxylate groups in directing calcite growth within copolymer worm gels is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…This resulted in fits that were not particularly sensitive to the R g of these dissolved chains. Nevertheless, this population was included for constancy with previously published data 62 and the fitted R g values were in the range 3 to 10 Å. This indicates that the low concentration of these dissolved chains is PKSPMA homopolymer (calculated R g of 14.4 and 18.6 Å for DP 32 and 53, respectively), rather than S x -B y copolymer chains.…”
Section: Preparation Of S X -B Y Nanoparticles With Varying Pbzma Dpmentioning
confidence: 78%
“…This resulted in fits that were not particularly sensitive to the R g of these dissolved chains. Nevertheless, this population was included for constancy with previously published data 62 and the fitted R g values were in the range 3 to 10 Å. This indicates that the low concentration of these dissolved chains is PKSPMA homopolymer (calculated R g of 14.4 and 18.6 Å for DP 32 and 53, respectively), rather than S x -B y copolymer chains.…”
Section: Preparation Of S X -B Y Nanoparticles With Varying Pbzma Dpmentioning
confidence: 78%
“…Fig. 4 shows the relationship between these two parameters determined for a series of aqueous dispersions of PHPMA-core worms prepared using a non-ionic PGMA stabilizer, 52 various binary mixtures of poly(methacrylic acid) (PMAA) and PGMA, 69 a non-ionic poly[N-(2-hydroxypropyl)methacrylamide] (PHPMAC) stabilizer 70 and the two zwitterionic PMPC stabilizers reported herein (see Fig. 3, Table 1, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, only very limited occlusion was observed for non-ionic poly(glycerol monomethacrylate) x -poly(benzyl methacrylate) y diblock copolymer nanoparticles. 25,37,38,45,46 However, we serendipitously found that poly(glycerol monomethacrylate)-functionalized gold nanoparticles can be efficiently incorporated within ZnO crystals, which will be discussed in more detail in the next section. Very recently, Kim et al reported that such gold nanoparticles can also be densely occluded within calcite crystals and also other host crystals such as calcium sulfate dihydrate and calcium oxalate monohydrate (Figure 6).…”
Section: Morphology and Sizementioning
confidence: 96%